2020
DOI: 10.3171/2018.12.jns182746
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal noninvasive evaluation in MRI-negative operculoinsular epilepsy

Abstract: OBJECTIVEPresurgical evaluation of patients with operculoinsular epilepsy and negative MRI presents major challenges. Here the authors examined the yield of noninvasive modalities such as voxel-based morphometric MRI postprocessing, FDG-PET, subtraction ictal SPECT coregistered to MRI (SISCOM), and magnetoencephalography (MEG) in a cohort of patients with operculoinsular epilepsy and negative MRI.METHODSTwenty-two MRI-negative patients were included who had focal ictal onset from the operculoinsular cortex on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…Generally, MRI is the preferred imaging technique for detecting the structural basis of epilepsy [ 9 , 10 ]. In the T2W fluid-attenuated inversion recovery (T2W FLAIR) imaging sequence, the cortical and subcortical hyper-signal is easier to detect [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, MRI is the preferred imaging technique for detecting the structural basis of epilepsy [ 9 , 10 ]. In the T2W fluid-attenuated inversion recovery (T2W FLAIR) imaging sequence, the cortical and subcortical hyper-signal is easier to detect [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, MAP revealed subtle abnormalities in 64.4% of patients, a finding generally consistent with previous literature ( 17 , 28 , 40 , 41 ). Detection rates of 45% for MRI-negative patients in insular epilepsy ( 42 ), 24.2% in extratemporal lobe epilepsy ( 43 ), 85% in FCD type II ( 24 ), and 43% in a large epilepsy cohort ( 17 ) have been reported using MAP. The slight variation of MAP detection rate among these studies was due to the difference in the definition of “MRI-negative” and the composition of patients included.…”
Section: Discussionmentioning
confidence: 99%
“…1 About 20% to 40% of adult intractable epilepsy patients have no lesion on MRI, which can portend a poor surgical outcome due to the challenge of seizure onset localization. [2][3][4] There are a number of preoperative predictors of seizure outcome following resective surgery for MRI-negative epilepsy. These include the localization of 18-fluorodeoxyglucose positron emission tomography (FDG-PET) and ictal single-photon positron emission tomography (SPECT) scans, as well as the concordance of multiple diagnostic modalities to a single brain region.…”
Section: Introductionmentioning
confidence: 99%